Implications of combined NOD2 and other gene mutations in autoinflammatory diseases - Nomani, Hafsa; Deng, Zuoming; Navetta-Modrov, Brianne; Yang, Jie; Yun, Mark; Aroniadis, Olga; Gorevic, Peter; Aksentijevich, Ivona; Yao, Qingping (Frontiers in Immunology, 2023)
NOD-like receptors (NLRs) are intracellular sensors associated with systemic autoinflammatory diseases (SAIDs). We investigated the largest monocentric cohort of patients with adult-onset SAIDs for coinheritance of low frequency and rare mutations in NOD2 and other autoinflammatory genes. Sixty-three patients underwent molecular testing for SAID gene panels after extensive clinical workups. Whole exome sequencing data from the large Atherosclerosis Risk in Communities (ARIC) study of individuals of European-American ancestry were used as control. Of 63 patients, 44 (69.8%) were found to carry combined gene variants in NOD2 and another gene (Group 1), and 19 (30.2%) were carriers only for NOD2 variants (Group 2). The genetic variant combinations in SAID patients were digenic in 66% (NOD2/MEFV, NOD2/ NLRP12, NOD2/NLRP3, and NOD2/TNFRSF1A) and oligogenic in 34% of cases. These variant combinations were either absent or significantly less frequent in the control population. By phenotype-genotype correlation, approximately 40% of patients met diagnostic criteria for a specific SAID, and 60% had mixed diagnoses. There were no statistically significant differences in clinical manifestations between the two patient groups except for chest pain. Due to overlapping phenotypes and mixed genotypes, we have suggested a new term, "Mixed NLR-associated Autoinflammatory Disease", to describe this disease scenario. Gene variant combinations are significant in patients with SAIDs primarily presenting with mixed clinical phenotypes. Our data support the proposition that immunological disease expression is modified by genetic background and environmental exposure. We provide a preliminary framework in diagnosis, management, and interpretation of the clinical scenario.